Srebrna zawieszka z Truso – dama w długiej sukni czy kapłanka? - Jagodziński, Marek Franciszek (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article revolves around a silver pendant depicting a female figure, discovered in Janów Pomorski and identified with the town of Truso. Such miniature figures, popular in inventories of Scandinavian grave fields, have been largely discussed with respect to their significance and meaning. The author indicates two rather neglected (or disregarded) elements of these representations: a long ribbon and a long object held by hand while the elbow is bent. They may be evidence of the female figure’s exceptional status, most probably that of a priestess.